Development of the Online and Blended Teaching Readiness Assessment (OBTRA) - Los, Ryan; De Jaeger, Amy; Stoesz, Brenda M. (Frontiers in Education, 2021)
The rapid shift to online teaching and learning in postsecondary education during COVID-19 forced institutions to provide additional support and resources to instructors, especially those who were teaching online for the first time. The Online and Blended Teaching Readiness Assessment (OBTRA) was designed to assess the perceptions and competencies of instructors undertaking the move to online teaching to identify strengths and limitations. The present study identified the underlying factor structure and evidence of construct validity of the OBTRA for a sample of 223 postsecondary instructors (data collected from November 2019 to January 2020). An exploratory factor analysis revealed 5 factors that were interpreted as Technology, Engagement & Communication, Pedagogy, Perceptions of Teaching Online, and Organization. OBTRA scores were also found to be positively correlated with scores obtained from measures of instructional practices and teacher efficacy. The next steps in the development of the OBTRA are to examine how it can be used to enable academic units to provide the most appropriate support and resources aligned with instructor needs and to guide instructors to the initial steps required for successful transition to online teaching.